(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The exchange rate is a monetary economic indicator that expresses a country’s economic performance. The exchange rate is the basic foundation on which the economies of any country in the world are built, whether developed or developing. As a result, most governments seek to implement regulations that ensure the currency exchange rate remains stable. To avoid the radical changes that currencies will endure during another period. The exchange rate also plays a prominent role in monetary policy, due to its use as an intermediate target, or as a tool, or simply as an indicator of the competitiveness of countries through its impact on components of economic growth such as investment, the degree of economic openness, the inflation rate, the narrow money supply, and the volume of exports. And the volume of imports, and foreign exchange reserves. Therefore, the primary goal of this study was to try to identify the nature of the exchange rate. As a result, in the first section, we discussed the concept of monetary policy, its most important tools, its most important goals, the exchange rate, and Iraq’s experience in the field of exchange during the period (1990-2023). While the second section was devoted to measuring the impact of monetary policy in achieving stability in the exchange rate of the Iraqi dinar against the US dollar using the vector model. correcting the mistake. The study concluded with some recommendations to reduce exchange rate fluctuations.